Interest rate determination in India: Empirical evidence on fiscal deficit. Interest rate linkages and financial crowding out - Lekha S. Chakraborty (Levy Economics Institute of Bard College, 2012)
Controlling for capital flows using the high-frequency macro data of a financially deregulated regime, this paper examines whether there is any evidence of the fiscal deficit determining the interest rate in the context of India. The period of analysis is FY 2006-07 (April) to FY 2011 (April). Contrary to the debates in policy circles, the paper finds that an increase in the fiscal deficit does not cause a rise in interest rates. Using the asymmetric vector autoregressive model, the paper establishes that the interest rate is affected by changes in the reserve currency, expected inflation, and volatility in capital flows, but not by the fiscal deficit. This result has significant policy implications for interest rate determination in India, especially since the central bank has cited the high fiscal deficit as the prime reason for leaving the rates unchanged in all of its recent policy announcements. The paper analyzes both long- and short-term interest rates to determine the occurrence of financial crowding out, and finds that the fiscal deficit does not appear to be causing either shorts and longs. However, a reverse causality is detected, from interest rates to deficits.
Keywords: C32; E62; H6; 330; fiscal deficit; asymmetric vector autoregressive model; financial crowding out